Innovation in food engineering : (CRC Press, 2010)
This book provides a comprehensive overview of modern processing technologies and their use to develop new or improved food products and ingredients that meet consumers increased demands for quality and safety. Each chapter in the Innovative Techniques section begins with a critical review of the fundamentals of the new or modified technique, its advantages, and relevant results. They include a description of the actual industrial scenario where the technique can be applied, emphasizing benefits and economical relevance of this sector.